A Language Survey of Northern Métis Languages: A Community-Based Language Revitalization Project - Saunders, Susan Jane (2015)
The purpose of the thesis is two-fold: to document the results of a language survey of Northern Métis languages which examines the language practices and attitudes of those Northern Métis people who participated, and to reflect upon the research process by examining the assumptions I bring to the research and my role and the role of other Masters level researchers in language revitalization projects. The research presented here has been conducted within the Community-based language revitalization (CBLR) research model (Czaykowska-Higgins 2009), a model which can be a powerful way to frame linguistic research and which is increasingly called upon when undertaking language revitalization projects. This thesis addresses the application of CBLR practices to a language revitalization project undertaken in collaboration with the North Slave Métis Alliance in the Northwest Territories, Canada. Along with positioning myself in the research, I provide an in-depth description of the historical, political, and social landscape in which the research takes place. My epistemologies and the CBLR model are informed by feminist and Native American methodologies, as well as participatory, participatory-action and action frameworks. Through this lens, I reflect on the academic context of language revitalization and offer my own model of collaborative language research which builds upon work done by Leonard & Haynes (2010). Applying this model, I present the results of the North Slave Métis Language Survey, conducted in 2013 in collaboration with the North Slave Métis Alliance. This thesis contributes to the body of work on Métis languages, and is the first to thoroughly examine and document the language practices of Métis people of the NWT. It also contributes to the growing body of work on CBLR research. Graduate